Analisis user interface dalam aplikasi perpustakaan digital “iPustaga” Dinas Kearsipan dan Perpustakaan Kabupaten Trenggalek - Saputro, Yahya Aji; atin, istiarni (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
This research aims to analyze the user interface of the iPustaga digital library application. Analysis of the application of user interfaces in applications using ten elements, namely connectivity, simplicity, directional, informative, interactivity, user friendliness, comprehensiveness, continuity. ), personalization (personalization), and internal (internal). The type of research used is descriptive qualitative. The research results show that the implementation of ten user interface elements in the iPustaga application is quite good. However, several features, such as Reading Friends, About the Application, Application Instructions, and the application display, such as color guidance from the display with fonts, need to be developed or updated regularly and fix bugs (errors) that often occur in the iPustaga application so that the application can be utilized maximally by the user. With the iPustaga application, it makes it easier for people, especially people in the Trenggalek area, to read activities that can be accessed anywhere and at any time.